"A question of fundamental, farreaching importance for all the future": German compensation payments as a result of the Herero War, 1904-1914 - Jacob Zollmann (An unresolved issue: genocide in colonial Namibia, 2024)
The German state has already paid compensation for damages caused by the Ovaherero war – to the German settlers and companies that were able to claim such war damages from 1904 onwards, as well as to some Africans. Attentive readers of Helmut Bley's seminal monograph on German colonial rule (1968) or of contemporary Wilhelmine texts and parliamentary minutes have long been aware of this.1 Yet, as far as can be seen, these possible precedents play no role in current political-legal and historiographical debates about possible German reparation payments to the Ovaherero and Nama in Namibia (and possibly also in Botswana and elsewhere). Even (legal) historians working on German colonial history in Namibia, or on the history of reparation payments, or on claims for reparations hardly took up these examples.2 This is remarkable, as they sparked heated debates in the Reichstag (Imperial parliament) and in the colony Deutsch-Südwestafrika (GSWA, German South West Africa) more than a century ago. In the following, after some conceptual legal discussions, the early beginnings of this colonial reparations debate, the main actors of this political struggle, and the (preliminary) results will be briefly analysed; well aware that the topic awaits a monographic treatment.
Keywords: 300; Krieg; Westafrika; Deutsches Kaiserreich; Kompensation; Zahlungsbereitschaft; Kolonie; südliches Afrika